Gender-sensitizing initiatives in the Philippines - Lee Esser, Andrea (Philippine Studies, 1995)
Although the "people-centered" approaches development that emerged in the 1980s as an improvement over earlier technocratic approaches, we are now seeing the extent to which project designs are limited by their failure to incorporate gender. besides being prone to lower success, projects which do not recognize gender as a variable often reinforce or actually increase gender inequality (Canadian Council for International Cooperation, et al. 1991; Thomas-slayter et al. 1990; Feldstein and Poats 1989; Overholt et al. 1985).This article examines the trend in the Philippines toward gender training as a means to refocus today's vision of development in order to recognize gender inequality and to challenge the systems which perpetrate patriarchy. It analyzes the different approaches and methods that dominate training and notes factors limiting impact.